2002
DOI: 10.1081/ja-120001975
|View full text |Cite
|
Sign up to set email alerts
|

Interest in and Obstacles to Pursuing Work Among Unemployed Dually Diagnosed Individuals

Abstract: Employment status is commonly used as a sign of stability in recovery and an outcome variable for substance abuse treatment and research. However, there has been little attention in the literature on the topic of work for the dually diagnosed (i.e., persons diagnosed with both substance use and mental health disorders). Data collected in 1999 are presented on expressed interest in and perceived barriers to pursuing work and on the utilization of vocational rehabilitation (voc-rehab) services among unemployed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 57 publications
0
24
0
4
Order By: Relevance
“…Laudet and colleagues (1) report that individuals with mental health problems often have fewer work-related skills, fewer interpersonal skills such as time management, impulse control, and self-presentation, and are likely to have more difficulty succeeding in the workplace than are individuals without mental health problems. These problems are amplified when an individual has both mental health and drug abuse problems.…”
mentioning
confidence: 97%
“…Laudet and colleagues (1) report that individuals with mental health problems often have fewer work-related skills, fewer interpersonal skills such as time management, impulse control, and self-presentation, and are likely to have more difficulty succeeding in the workplace than are individuals without mental health problems. These problems are amplified when an individual has both mental health and drug abuse problems.…”
mentioning
confidence: 97%
“…Several studies found that substance use disorders do not impair capacity to work beyond the already significant impairments due to severe mental illness (Bell et al 2002;Cook et al 2007;Drebing et al 2002;Laudet et al 2002;Pickett-Schnek et al 2002;Sengupta et al 1998). Drebing and colleagues found no added risk of non-compliance with vocational rehabilitation associated with a co-occurring substance use disorder compared to individuals with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the strong evidence to date of the effectiveness of Supported Employment programs, gaps in knowledge remain, especially for persons with co-occurring mental and substance disorders (Laudet et al 2002). There has been little examination concerning which consumers get referred to Supported Employment programs and which mental health consumers do not get referred.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zieke werklozen hebben minder kans op werkhervatting dan gezonde werklozen. 7 Verder is gebleken dat geestelijke gezondheidsklachten in het algemeen 19 en psychosomatische klachten in het bijzonder 20 werkhervatting belemmeren.…”
Section: Fac To R E N D I E W E R K H E Rvat T I N G B E ï N V Lo E Dunclassified